Paramedic Intubation Experience Is Associated With Successful Tube Placement but Not Cardiac Arrest Survival - Dyson, K.; Bray, Janet; Smith, K.; Bernard, S.; Straney, L.; Nair, R.; Finn, J. (Mosby, 2016)
© 2017 American College of Emergency Physicians.Study objective: Paramedic experience with intubation may be an important factor in skill performance and patient outcomes. Our objective is to examine the association between previous intubation experience and successful intubation. In a subcohort of out-of-hospital cardiac arrest cases, we also measure the association between patient survival and previous paramedic intubation experience. Methods: We analyzed data from Ambulance Victoria electronic patient care records and the Victorian Ambulance Cardiac Arrest Registry for January 1, 2008, to September 26, 2014. For each patient case, we defined intubation experience as the number of intubations attempted by each paramedic in the previous 3 years. Using logistic regression, we estimated the association between intubation experience and (1) successful intubation and (2) first-pass success. In the out-of-hospital cardiac arrest cohort, we determined the association between previous intubation experience and patient survival. Results: During the 6.7-year study period, 769 paramedics attempted intubation in 14,857 patients. Paramedics typically performed 3 intubations per year (interquartile range 1 to 6). Most intubations were successful (95%), including 80% on the first attempt. Previous intubation experience was associated with intubation success (odds ratio 1.04; 95% confidence interval 1.03 to 1.05) and intubation first-pass success (odds ratio 1.02; 95% confidence interval 1.01 to 1.03). In the out-of-hospital cardiac arrest subcohort (n=9,751), paramedic intubation experience was not associated with patient survival. Conclusion: Paramedics in this Australian cohort performed few intubations. Previous experience was associated with successful intubation. Among out-of-hospital cardiac arrest patients for whom intubation was attempted, previous paramedic intubation experience was not associated with patient survival.